Marketisation policies in the neoliberal era: How culture and governance structures affect the introduction of market principles in local care policies. (May 2023) - Och, Ralf; Pfau-Effinger, Birgit
Confronted with the problem of ageing populations since the 1990s, many European welfare states have massively expanded public support for the care of the elderly. This expansion occurred during the neoliberal era in which the marketisation of social services was high on European countries' political agendas. There are many studies concerned with cross-national differences between national policies regarding the marketisation of care, but little comparative research has been carried out at the local level. This article is innovative in that it explores the role of welfare cultures and local governance structures in local policies regarding the marketisation of long-term care (LTC). We present the findings of a historical comparative case study of four medium-sized cities in Germany for the period 1995–2007. Our empirical study took a multi-level approach to exploring the extent to which the central German state affords local governments operational autonomy for LTC marketization, then analysed the differences in local policies regarding LTC marketisation. According to our findings, German LTC policies are rather centralised and afford local governments operational autonomy towards marketisation only in a few fields. In these fields, local LTC policies differ substantially between eastern and western German cities. We find that differences in the relevant political actors' main cultural ideas and in local governance structures contribute to this variation, whereas the financial and demographic differences that were analysed do not.